Perancangan Aplikasi untuk Evaluasi Implementasi Arsitektur Enterprise - Noviansyah, Beri; Fauzi, Cholid (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
The evaluation process of an enterprise architecture implementation is very important. This process will assess whether the company that has been implemented is still in accordance with organizational goals or not. The hybrid evaluation method is a method used as the basis for developing evaluation applications because this method can assess all artifacts of the enterprise architecture. The methodology used in this study refers to the Design Science Research Methodology (DSRM) method with a system development model following the flow of a waterfall. System modeling tools using UML. The results of the research are in the form of an initial design of the application that will be made which includes use case diagrams, class diagrams, and interface design. The results of this design can be used by both academics and academics, who will evaluate the implementation of enterprise architecture.